Case Report: Diagnostic overlap of OHVIRA syndrome and Gartner duct cyst: challenges in imaging and management - Zhao, Junfeng; Bao, Yaqing; Gong, Linglu; Shi, Zhan; Chen, Xiaoqiang; Li, Yan (Frontiers in Pediatrics, 2025)
This case series explores the diagnostic overlap between OHVIRA syndrome (obstructed hemivagina and ipsilateral renal anomaly) and Gartner duct cyst (GDC) with ipsilateral renal dysplasia in two prepubertal girls. Both cases exhibited similar imaging features on CT and MRI—including unilateral renal agenesis, ectopic ureter with abnormal insertion, cystic lesions posterolateral to the bladder— which led to significant diagnostic challenges. Despite differing in pathology, the overlap in embryologic origins and imaging findings made differentiation difficult. This series underscores the importance of comprehensive imaging and a multidisciplinary approach for accurate diagnosis. Current management strategies are discussed, highlighting the need for individualized treatment plans in prepubertal patients with complex genitourinary anomalies.